Effects of video-based training on anticipation and decision-making in football players: A systematic review - Zhao, Jie; Gu, Qian; Zhao, Shuo; Mao, Jie (Frontiers in Human Neuroscience, 2022)
The training of athletes’ anticipation and decision-making skills has received increasing attention from researchers, who developed and implemented training programs to achieve this. Video-based training has become a popular method in anticipation and decision-making skills training. However, little is known about the benefits of implementing video-based training in soccer. This systematic review considered the results of studies on video-based training aiming to develop decision-making and anticipation skills in football players, and analyzed its effects. Literature published up to March 2022 was systematically searched on the scientific electronic databases Web of Science, PubMed, Scopus, SportDiscus, and Google Scholar. In total, 5,749 articles were identified. After screening the records according to the set exclusion and inclusion criteria, ten articles were considered eligible, including six longitudinal studies and four acute studies. Eight of the ten included studies (80%) showed that video-based training (VBT) group performance in anticipation or decision-making skills was significantly better at post-test than at pre-test, as evidenced by improvements in response accuracy (RA), response times (RT), mean distance scores (MDS) and passing decision-making performance. In six studies that included the no video training group (NVBT), results showed that athletes in the VBT group performed better in anticipation or decision-making skills than in the NVBT group, as evidenced by improvements in RA and RT performance. The studies used different methods for video-based training, both explicit and implicit training effectively improved participants’ anticipation and decision-making skills. In addition, the implementation of the “first-person” perspective (i.e., the player’s perspective) and virtual reality improved the presentation of video stimuli, effectively improving anticipation and decision-making. The findings of this review suggest that video-based training is beneficial in developing anticipation and decision-making judgments in football players. However, some findings were inconsistent with previous studies due to differences in intervention duration and experimental protocols, and further studies are needed. Furthermore, future research should actively seek to design appropriate retention tests and transfer tests to truly understand the benefits of video-based training for athletes.